2010
DOI: 10.1039/c0cp00643b
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar redox behaviour, field-effect mobility and transistor switching of the low-molecular azo glass AZOPD

Abstract: We present electrochemical and spectroelectrochemical data for the bipolar azo compound N,N'-diphenyl-N,N'-bis[4-(phenylazo)phenyl]-4,4'diaminobiphenyl (AZOPD) demonstrating reversible bipolar redox behaviour with a bandgap of 2.1 eV. The reduced species formed upon two-electron transfer can be described as bis(radical anion) as was confirmed by comparison with a reference compound with only one azo chromophore. Hole and electron transport behaviour in amorphous films was demonstrated by the fabrication of org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Recent studies, in contrast, have used photochromic molecules directly as transistor channels, aiming at improving the on/off ratios. Arlt et al used an azobenzene derivative for a channel layer, but the hole mobility and on/off ratio were still low: 9.8 × 10 −6 cm 2 Vs −1 and I on / I off = 2.5 [120]. Hayakawa et al used a diarylethene molecule as the transistor channel to give a direct impact of photochromism on the drain current [121].…”
Section: Light-receiving Ofetsmentioning
confidence: 99%
“…Recent studies, in contrast, have used photochromic molecules directly as transistor channels, aiming at improving the on/off ratios. Arlt et al used an azobenzene derivative for a channel layer, but the hole mobility and on/off ratio were still low: 9.8 × 10 −6 cm 2 Vs −1 and I on / I off = 2.5 [120]. Hayakawa et al used a diarylethene molecule as the transistor channel to give a direct impact of photochromism on the drain current [121].…”
Section: Light-receiving Ofetsmentioning
confidence: 99%
“…Zheng et al first reported that pure (2 R ,4 S )-difenoconazole has better bioactivity and lower ecotoxicity compared with its stereoisomers, showing excellent environmental behaviors in vegetables and soil . Wu’s group found that cis -dichlorodiamineplatinum­(II) is an efficient drug to cancer cells, whereas its trans form does not work at all. , Fuhrmann-Lieker et al synthesized an azo compound with photosensitivity via E/Z isomerization and it can thus be regarded as a multifunctional organic field-effect transistor . Considering these attractive properties as well as miscellaneous applications in life and material sciences, obtaining a pure isomer is very important and intriguing even though it is so tough to synthesize and separate pure E isomer and Z isomer.…”
Section: Introductionmentioning
confidence: 99%
“…A very interesting molecule for this work is the low molecular azo glass named N,N’ -bis(phenyl)- N,N’ -bis((4-phenylazo)-phenyl)benzidine (AZOPD), which can be used for photo-induced structuring for holographic data storage devices [ 52 ]. Because of its extraordinary electrochemical properties it can be considered as a multifunctional organic semiconductor (e.g., as an hole transporting material in organic light emitting devices (OLED) or as a photo-switch in organic transistors) [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%